Approach to Computer Ethics in Higher Education - Aguilera Borjas, Madelín; Aguilera Almaguer, Osmany; Pérez Alí Osmán, Edilberto de Jesús (Espergesia, 2020)
The accelerated changes that occur in the society Information and Communication Technologies (ICT), are causing an intense cultural revolution for humanity, while they face major challenges and offer enormous potential to contribute to the development of Higher Education. In this sense, they enable transformations to offer up-to-date and quality education, in order to generate enriched learning environments. For every university institution, it is a challenge to achieve an Information Ethics in accordance with the moral and the principles derived from our state, for this purpose, we intend with the present material to present an approach to Computer Ethics in Higher Education, especially in the University of Holguin For this, it is based on criteria derived from scientific works carried out by some national and international authors in order to reach precise conclusions on the subject. Its level of application is precise from the imposition of ethics not as a fashion, but as a necessity, an indispensable tool to face the new challenges that arise in the face of scientific-technological development. Within this context, there is a positive impact on the ethical and responsible behavior of computer users during the use of ICT at the University of Holguin, which is a fundamental factor in achieving the success of our institution.